ANALISIS KUALITAS PELAYANAN DAN PENGENDALIAN KUALITAS JASA BERDASARKAN PERSEPSI PENGUNJUNG - Sudarno, Sudarno; Rusgiyono, Agus; Hoyi, Abdul; Listifadah, Listifadah (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2011)
One of the factors which determine customer safisfaction is costumer perceive about service quality that focus to five service quality dimension that are tangible, reliability, responsiveness, assurance, and empathy. This research study service serve quality at UPT Perpustakaan Universitas Diponegoro Semarang with object to know customer perceive with respect to some variables in service quality dimension and satisfaction level. Importance-Performance Analysis used to map relation between importance with performance of respective variables to be and see gap between performance with importance of them variables. Customer Satisfaction Index (CSI) used to analyze all satisfaction respondent level. The T2 Hotelling control chart to know servicing process stability with respect to costumer perceive. Research result shows that the gap is all negative value. It means library performance that represented by 21 variables include 5 service quality dimension still under expected costumer. The value CSI is 62,903% that meaning at enough satisfaction criterion. There are five points at above upper control limit in the T2 Hotelling control chart. Therefore it can be said that process havenâ€™t been controlled by statistical. Â Keywords: Service Quality, Importance-Performance Analysis, Customer Satisfaction Index,Â Hotelling T2 Control Chart.